Water Isotopic Signature of Surface Snow Metamorphism in Antarctica. Issue 17 (3rd September 2021) - Casado, Mathieu; Landais, Amaelle; Picard, Ghislain; Arnaud, Laurent; Dreossi, Giuliano; Stenni, Barbara; Prié, Frederic
Abstract: Water isotope ratios of ice cores are a key source of information on past temperatures. Through fractionation within the hydrological cycle, temperature is imprinted in the water isotopic composition of snowfalls. However, this signal of climatic interest is modified after deposition when snow remains at the surface exposed to the atmosphere. Comparing time series of surface snow isotopic composition at Dome C with satellite observations of surface snow metamorphism, we found that long summer periods without precipitation favor surface snow metamorphism altering the surface snow isotopic composition. Using excess parameters (combining D, 17 O, and 18 O fractions) allow the identification of this alteration caused by sublimation and condensation of surface hoar. The combined measurement of all three isotopic compositions could help identifying ice core sections influenced by snow metamorphism in sites with very low snow accumulation. Plain Language Summary: Water isotopes in ice core records are often used to reconstruct past climate temperature variations. Classically, the temperature signal is thought to be imprinted in water isotopes of precipitation, and then archived in the ice core as it falls, and in cold areas of Antarctica, piles up for very long period. Here, we show that the surface snow isotopic composition varies in between precipitation events, suggesting that there might be more than one contribution to the isotopic signal in ice core records. This is particularly important for low accumulation sites, where the snow at the surface remains exposed for very long time periods. The combined use of several isotopic ratios in surface snow helps us disentangle the processes that create this signal. Key Points: During summer without precipitation, intense snow metamorphism shows a strong water isotopic signature During summer without precipitation, intense snow metamorphism shows a strong water isotopic signature The d‐excess and 17 O‐excess of the snow is a proxy of snow metamorphism for low accumulation regions